1994
DOI: 10.1017/s0890037x00039774
|View full text |Cite
|
Sign up to set email alerts
|

Fall Application of Prodiamine for Spring Crabgrass (Digitariaspp.) Control

Abstract: Fall application of a PRE herbicide offers professional lawncare applicators additional flexibility in scheduling necessary weed control operations. A 3-yr field study was established on common Kentucky bluegrass in Urbana, IL to examine the effectiveness of fall- or spring-applied prodiamine and DCPA for spring large and smooth crabgrass control. Prodiamine was effective for crabgrass control in turf (≥ 91% control) when applied in spring at ≥ 0.4 kg/ha or when it was applied in the fall at ≥ 0.6 kg/ha (≥ 82%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Previously, several researchers found prodiamine rates of 0.5 to 2 lb/acre highly effective on large crabgrass (Bhowmik 1988;Bhowmik and Bingam 1990;Duray and Davies 1987;Enache and Unicki 1987;Fermanian and Haley 1994;Fretz and Sheppard 1980). In Alabama, USA, Wehtje et al (2010) reported $ 95% control of large crabgrass 6 weeks after prodiamine application at 0.7 lb/acre.…”
Section: Weed Controlmentioning
confidence: 99%
“…Previously, several researchers found prodiamine rates of 0.5 to 2 lb/acre highly effective on large crabgrass (Bhowmik 1988;Bhowmik and Bingam 1990;Duray and Davies 1987;Enache and Unicki 1987;Fermanian and Haley 1994;Fretz and Sheppard 1980). In Alabama, USA, Wehtje et al (2010) reported $ 95% control of large crabgrass 6 weeks after prodiamine application at 0.7 lb/acre.…”
Section: Weed Controlmentioning
confidence: 99%
“…The few studies that directly compared spring and autumn applications in the northern U.S. were conducted in USDA Hardiness Zone 5 (research presented herein was in Zone 7). These studies determined pendimethalin, dithiopyr, and prodiamine were sometimes less effective when applied in November than in the spring (Fermanian & Haley, 1994; Reicher & Throssell, 1993; Reicher et al., 2011). More conclusively, Reicher, Sousek, and Gaussion (2014) found single applications of dithiopyr, prodiamine, and pendimethalin were less effective when applied in fall or late winter compared with the spring in Nebraska.…”
Section: Introductionmentioning
confidence: 99%
“…Turf managers routinely use it to control annual grasses on mature turfs. Previous evaluations of prodiamine have indicated a long soil persistence and high activity on susceptible species (4,5,12,14). This long persistence raises the question of prodiamine's effect on juvenile or newly established turf.…”
Section: Introductionmentioning
confidence: 99%